Child Development and Early Interaction: PERL Research Protocol, a Preventive Home Visiting Program, Randomized Controlled Trial in France - Buchheit, Sophie; Kabuth, Bernard; Colombo, Marie-Christine; Ligier, Fabienne (Frontiers in Psychiatry, 2021)
Background: Early childhood is a key period for reducing the social inequalities that affect health. Some parenting support and home visitation programs have proven to be effective in assisting parents during this period. France's Protection Maternelle et Infantile (maternal and child welfare) services (PMIs) are at the heart of this primary prevention and may adapt their intervention to improve parenting support. In this manuscript, we describe the protocol of the PERL study, an intervention based on a home visiting program. Method and design: The PERL study is a single-center, randomized, controlled interventional trial. The aim was to assess the impact of a preventive home visiting program on the development of young children and parent-baby interaction. Visits were made by PMI nurses to 64 randomly recruited families from the general population. All families who had a baby born after 37 weeks of pregnancy between September 2018 and December 2019, and who resided in the trial area were eligible. Participants were randomly allocated to the intervention group or the control group. The PMI nurses made 12 home visits in the first year, 6 in the second year, and 4 in the third and fourth years of the child's life. Primary and secondary outcomes were measured when the child was 4 and 24 months old. These measurements recorded (i) the child's developmental milestones, in particular, language and socio emotional skills, (ii) early interaction, maternal sensitivity, and attachment patterns, (iii) maternal psychopathology including depression. Discussion: This study aims to assess the impact of home visits, made by specifically-trained and supervised nurses, on the child's development and parent-child interactions. Such interventions are complementary to other preventive programs addressing the impact of social inequalities on perinatal health. Placing nurses' professional skills at the center of this project may prove an effective and cost-saving intervention compared to existing programs. The study proposes a prevention model that is in keeping with the principle of reducing social inequalities in health by providing support from the earliest age through public service. Clinical Trial Registration: The clinical trial number is NCT03506971, registered on April 24, 2018.